Endoleak and Pseudoaneurysm Formation in the Setting of Stent Graft Infection Following Endovascular Uretero-Arterial Fistula Repair: The Dreaded Complication - Perrenoud, Abby L (Cureus, 2020)
The complication of uretero-arterial fistula after prolong ureteral stenting is well recognized. The treatment is primarily endovascular stenting across the fistulous communication accepting the potential risk of stent graft infection. Herein we present a case of a 71-year-old female who developed an uretero-arterial fistula after prolong ureteral stenting and exchanges following ileal conduit obstruction. Initial treatment with left common iliac stenting controlled the hematuria, but only temporarily. Repeat angiography revealed a type 1b endoleak requiring stent extension. Unfortunately, persistent hematuria necessitating further angiography showed the development of a saccular pseudoaneurysm around the stent graft requiring proximal stent extension. A nuclear medicine indium 111-tagged white blood cell scan with single-photon emission CT (SPECT)/CT confirmed stent graft infection. Conservative therapy with antibiotics failed, causing graft failure that ultimately required bypass surgery.